Aposymbiotic Specimen of the Photosynthetic Sea Slug Elysia crispata - Cartaxana, Paulo (2022)
Elysia crispata is a sacoglossan sea slug that retains intracellular, functional chloroplasts stolen from their macroalgal food sources. Elysia crispata juveniles start feeding on the algae following metamorphosis, engulfing chloroplasts and turning green. In laboratory-reared animals, we report one juvenile "albino" specimen unable to retain chloroplasts. Within 6 weeks post-metamorphosis, the aposymbiotic sea slug was significantly smaller than its chloroplast-bearing siblings. This evidence highlights that chloroplast acquisition is required for the normal development of E. crispata.